Lesson Study: An Approach to Increase the Competency of Out-of-Field Mathematics Teacher in Building the Students Conceptual Understanding in Learning Mathematics - Aini Haziah Amirullah (Universitas Riau, 2018)
The study was conducted to observe the effectiveness of Lesson Study as an approach used to increase the skills of an out-of-field Mathematics teacher or ‘non-optional’ teacher, in building the conceptual understanding among students during the teaching and learning process. This qualitative case study was conducted using a Lesson Study approach involving a novice Mathematics teacher who is also a non-optional teacher, in a district of Seremban, Negeri Sembilan, Malaysia. An expert in Mathematics, School Improvement Specialist Coach(SISC+) was involved in the classroom observation. There were three different sessions conducted and the observation was recorded. Transcripts were prepared for the three observations for comparison and analytical review on the learning and teaching process with the Excellent Mathematics Teacher. It was observed that the Mathematics teacher’s competency improved after evaluating the students’ response and achievements after the learning session. Teachers who were involved,developed their skills and expertise through discussions during the Lesson Planning, teaching and review sessions. The teachers are more confident in addressing students issue as well as class control ‘Lesson Study’ approach had contributed to upgrade the skills and efficiency of the non-optional Mathematics teachers as well as enriching the learning strategy, approach and methodology.